Implementation of Integrated Isbat Nikah in Gresik Regency from the Perspective of Maqāṣid al-Sharī'ah - Fajriyah, Intan Nur; Musyafaah, Nur Lailatul (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Abstract: The large number of unregistered marriages in Gresik causes problems in population administration. Therefore, the Gresik Religious Court and the Gresik Regency Government collaborated to hold an Integrated Isbat Nikah for married couples who have not registered their marriage. This study aims to examine the implementation of the Integrated Isbat Nikah in Gresik Regency from the perspective of Maqāṣid al-Sharī'ah. This research uses a qualitative approach with a type of field research. Data were obtained through interviews, document studies, and literature studies. The collected data were analyzed descriptively with the theory of Maqāṣid al-Sharī'ah. The study concluded that the integrated isbat nikah was conducted in accordance with Gresik Regent Regulation Number 74 of 2023 and PERMA Number 1 of 2015, which concern integrated services for circumference sessions. The main goal is to provide legal certainty for marital status, protect women and children, and ensure easy access to marriage legality at no cost. The trial was held in a religious court, and participants obtained three legal products simultaneously: court determination, marriage book, and population documents (KTP, KK, and child birth certificate). From the perspective of Maqāṣid al-Sharī'ah, this program embodies the five main objectives of the shari'a (al-uṣūl al-khamsah), namely the maintenance of religion (ḥifẓ al-dīn), the soul (ḥifẓ al-nafs), intellect (ḥifẓ al-'aql), heredity (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). The most dominant aspects reflected in the implementation of this program are ḥifẓ al-nasl and ḥifẓ al-māl, because both directly protect the clarity of the child's destiny and the economic rights of the family. Keywords: Integrated Isbat Nikah, Religious Courts, Maqāṣid al-Sharī'ah, Protection of Descendants, Islamic Family Law.   Abstrak: Banyaknya perkawinan yang tidak tercatat di Gresik, menimbulkan masalah dalam administrasi kependudukan. Karena itu, Pengadilan Agama Gresik dan Pemerintah Kabupaten Gresik bekerjasama mengadakan Isbat Nikah Terpadu bagi pasangan suami istri yang belum mencatatkan perkawinannya. Penelitian ini bertujuan mengkaji pelaksanaan Sidang Isbat Nikah Terpadu di Kabupaten Gresik dalam perspektif Maqāṣid al-Sharī‘ah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan. Data diperoleh melalui wawancara, studi dokumen dan studi literatur. Data yang terkumpul dianalisis secara deskriptif dengan teori Maqāṣid al-Sharī'ah. Hasil penelitian menyimpulkan bahwa isbat nikah terpadu dilaksanakan berdasarkan Peraturan Bupati Gresik Nomor 74 Tahun 2023 dan PERMA Nomor 1 Tahun 2015 tentang pelayanan terpadu sidang keliling. Tujuan utamanya ialah memberikan kepastian hukum terhadap status perkawinan, perlindungan terhadap perempuan dan anak, serta kemudahan akses legalitas perkawinan tanpa biaya. Sidang dilakukan di pengadilan agama dan peserta memperoleh tiga produk hukum secara bersamaan: penetapan pengadilan, buku nikah, serta dokumen kependudukan (KTP, KK, dan akta kelahiran anak). Dari perspektif Maqāṣid al-Sharī‘ah, program ini mewujudkan lima tujuan pokok syariat (al-uṣūl al-khamsah), yaitu pemeliharaan agama (ḥifẓ al-dīn), jiwa (ḥifẓ al-nafs), akal (ḥifẓ al-‘aql), keturunan (ḥifẓ al-nasl), dan harta (ḥifẓ al-māl). Aspek yang paling dominan tercermin dalam pelaksanaan program ini adalah ḥifẓ al-nasl dan ḥifẓ al-māl, karena keduanya secara langsung melindungi kejelasan nasab anak serta hak-hak ekonomi keluarga. Kata kunci: Isbat Nikah Terpadu, Pengadilan Agama, Maqāṣid al-Sharī‘ah, Perlindungan Keturunan, Hukum Keluarga Islam.